MEDIEVAL HERITAGEAS A SOCIOLOGICAL FOUNDATION OF DEFINING THE SERBIAN ELITE IN THE SIXTEENTH CENTURY - Ненад Лемајић (Истраживања, 2012)
The paper discusses the sociological analysis of the elite formation in the Middle Ages in the territory of Serbian states, and the acceptance of the inheritance by the emerging leading groups of the Serbian society. After the disappearance of the medieval Serbian states in the Ottoman Empire, partially in the Christian countries in which Serbian people he lived, was grown into a new social class dealing with the warrior profession on behalf of the state in which he lived. This paper analyzes the extent to which he inherited the medieval legacy of the Serbian ruling class and the state.